On- and off-shelf diving effort of juvenile elephant seals from Pennsula Valds determined by light loggers - Eder, Elena Beatriz; Lewis, Mirtha Noemi; Marin, Maria Rosa; Campagna, Claudio (Journal of Mammalogy)
The shallow Patagonian Shelf off Pennsula Valds limits the dive depth of southern elephant seals (Mirounga leonina) to <100 m, an unusual circumstance for this deep-diving species. Beyond the shelf water depths of >1,000 m enable the seals to forage deeper and use the entire water column. We compared the diving pattern of 10 juveniles instrumented with lighttemperature loggers to determine if diving effort, measured as dive durations longer than the estimated aerobic dive limit, differed between on-shelf and off-shelf waters. The productive Patagonian Shelf, an environment where juveniles showed lower diving effort, also was used commonly by older seals, which likely displaced juveniles off-shelf periodically, where they exhibited increased diving effort. Fil: Eder, Elena Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Lewis, Mirtha Noemi. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Marin, Maria Rosa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Campagna, Claudio. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina. Wildlife Conservation Society; Argentina